National government and special capital government relations in covid-19 crisis communication - Suswanta, Suswanta; Setiawan, Anang; Widayat, Rossi Maunofa (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
This study aims to analyze the phenomenon of miscommunication between the central government and the Special Capital Region of Jakarta in handling the COVID-19 pandemic, using the lens of Situational Crisis Communication Theory (SCCT). The COVID-19 crisis in Indonesia revealed significant inconsistencies in policy communication, particularly through social media, leading to confusion in public understanding and response. This research focuses on Twitter as a critical platform used by both the Ministry of Health and the Jakarta government. Employing a descriptive qualitative method, the study analyzed social media content from June to September 2021 using NVivo 12 Plus software. The findings demonstrate that while both institutions engaged in digital communication, the Ministry of Health adopted a more centralized, formal approach, whereas the Jakarta government employed a localized and interactive strategy. Despite these efforts, coordination was often reactive and lacked synchronization, resulting in fragmented messaging and weakened public trust. Word cloud and cluster analyses reveal that terms like “Indonesia,” “COVID,” and “WE” were frequently used to evoke unity, but were insufficient to bridge the rhetorical-practical gap in crisis management. The study concludes that although Twitter has potential as a tool for crisis communication, the absence of coherent strategy and coordination between central and regional governments undermined its effectiveness. Improved integration of SCCT principles and harmonized communication frameworks are essential to strengthen future governmental responses in public health emergencies.